2019
DOI: 10.1371/journal.pone.0218523
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution of dominant malaria vector species in tropical region under climate change scenarios

Abstract: Risk assessment regarding the distribution of malaria vectors and environmental variables underpinning their distribution under changing climates is crucial towards malaria control and eradication. On this basis, we used Maximum Entropy (MaxEnt) Model to estimate the potential future distribution of major transmitters of malaria in Nigeria— Anopheles gambiae sensu lato and its siblings: Anopheles gambiae sensu stricto, and Anopheles arabiensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…aegypti in relation to dengue fever incidence will increase in the future in Africa, which is in agreement with other studies [4,7,8,19].WHO also stated that the endemicity of dengue fever incidence will increase, and outbreak could occur in areas where they are currently unknown due to climate changes [36]. Changes in temperature have been predicted to determine mosquito-borne disease occurrence, primarily through changes in mosquito reproduction, development and survival, and pathogen incubation rates and survival [2,6,14,17,37,38]. Our study identified that temperature is the most important climatic variable, which collectively determined 70.8% of the potential distribution of Ae.…”
Section: Discussionsupporting
confidence: 83%
“…aegypti in relation to dengue fever incidence will increase in the future in Africa, which is in agreement with other studies [4,7,8,19].WHO also stated that the endemicity of dengue fever incidence will increase, and outbreak could occur in areas where they are currently unknown due to climate changes [36]. Changes in temperature have been predicted to determine mosquito-borne disease occurrence, primarily through changes in mosquito reproduction, development and survival, and pathogen incubation rates and survival [2,6,14,17,37,38]. Our study identified that temperature is the most important climatic variable, which collectively determined 70.8% of the potential distribution of Ae.…”
Section: Discussionsupporting
confidence: 83%
“…is finding is consistent with studies that show that in arid and semiarid areas, moisture availability is a primary modulator of vegetation growth [48,51,53,54,63].…”
Section: Annual Correlations Between the Ndvi And Precipitationsupporting
confidence: 92%
“…e average precipitation declined sharply in 2004 and increased again from 2004 to 2012, after which it decreased again with significant fluctuations during this period ( Figure 5(d)). e highest annual precipitation occurred in 2012 for the entire study period which also coincided with extensive nationwide flooding Advances in Meteorology and spread of epidemics in some cases [61][62][63]. Generally, rainfall exhibited positive trend in about 18.36% of total vegetated areas, out of which only about 0.47% was significant ( Figures 6(b) and 6(d)).…”
Section: Annual Correlations Between the Ndvi And Precipitationmentioning
confidence: 74%
See 1 more Smart Citation
“…However, among the sub-Saharan African countries, Nigeria has the highest share of the global burden of malaria disease [3]. More than 95% of the malaria cases in Nigeria are caused by P. falciparum [10][11][12], mostly occurring in children under the age of 5 years [3,10,12]. At present almost more than 70% of the Nigerian population live in endemic areas [13,14].…”
Section: Introductionmentioning
confidence: 99%